Comparison of Explicit and Implicit Finite Element Methods and its Effectiveness for Drop Test of Electronic Control Unit. (2017) - Balakrishnan, Kamarajan; Sharma, Arvind; Ali, Rajib
Abstract: Engine control unit consists of many electronic components like capacitors, inductor coils, Ball Grid Array (BGA) and Ceramic chips which are prone to fail during drop. As per ISO 16750-3 standard electronic components are dropped from one meter height on rigid wall in six different dimensional axis to check the reliability of the system[4] . Unless the ECU mechanical structure fails or components inside housing separates from PCB drop failures cannot be noticed. Designing drop reliable electronic components are critical to improve the quality of ECU and vehicle. This paper discusses the effectiveness of four simulation methods used to simulate electronic control unit (ECU) drop test. Explicit and Implicit simulation methods are considered in this study. Under implicit simulation technique full transient, steady state static and mode super position methods are studied and they are compared with explicit method. Explicit simulation method is conditionally stable whereas implicit methods are un-conditionally stable, this makes the explicit method computationally costlier and time consuming. Convergence and absence to capture the dynamic response are the major challenges in implicit method. For this study the electronic control unit is simplified with bare printed circuit board (PCB) and frame for drop simulation. PCB in-plane strains and displacements are evaluated for one meter height drop on rigid floor and all corresponding results are compared to find the effectiveness of each method.